2003
DOI: 10.1089/107555303321222991
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Physical Research in Homeopathy

Abstract: Most physical experiments of homeopathic preparations were performed with inadequate controls or had other serious flaws that prevented any meaningful conclusion. Except for those of high quality, all experiments should be repeated using stricter methodology and standardization before they are accepted as indications of special features of homeopathic potencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…A global discrimination of frequencies that are 'sensitive' or 'insensitive' to aqueous potencies is obvious. We followed criteria for quality standards that were often absent in physical basic research on homeopathy [11], among them randomization and blinding, replicating, and an adequate statistical analysis, after preparation and storage influences have been determined [13]. Special care was taken to standardize samples and measurements: Predefined procedures were observed and contamination was tracked by conductivity measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A global discrimination of frequencies that are 'sensitive' or 'insensitive' to aqueous potencies is obvious. We followed criteria for quality standards that were often absent in physical basic research on homeopathy [11], among them randomization and blinding, replicating, and an adequate statistical analysis, after preparation and storage influences have been determined [13]. Special care was taken to standardize samples and measurements: Predefined procedures were observed and contamination was tracked by conductivity measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Finally (E, F) we looked for influences of container materials and sample ages. Plain solvent, potentized to remedy potency, served as control [11]. Each experiment included 8 samples: 3 independent preparations each of remedy C30 and control C30 that were measured blind, and 2 baseline samples of plain solvent, measured not blind before and after the potentized samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of the former is a 2003 meta-analysis of experiments, 14 each examining the ability of homeopathic preparations to alter physical properties of solvents. Of the 44 papers reviewed, 38 claimed to have found positive results for homeopathy, meaning that the dilutions were active in some way.…”
Section: Physical Experiments In Dilution Researchmentioning
confidence: 99%
“…This study clearly showed the complex interdisciplinary expertise required to conduct high-quality research in homeopathy. 71 A review of all extant literature on physical studies trying to identify a materially active component and methodologically rating the studies concluded that most studies were rather weak from a methodological point of view 72 (see Table 1 for an overview). Together, this very weak literature shows that no viable evidence for stable water clusters (required for so called "water memory") currently exists.…”
Section: Basic Researchmentioning
confidence: 99%